A tale of two morphs: developmental patterns and mechanisms of seed coat differentiation in the dimorphic diaspore model Aethionema arabicum (Brassicaceae) - Arshad, Waheed; Lenser, Teresa; Wilhelmsson, Per K I; Chandler, Jake O; Steinbrecher, Tina; Marone, Federica; Pérez, Marta; Collinson, Margaret E; Stuppy, Wolfgang; Rensing, Stefan A; Theißen, Günter; Leubner-Metzger, Gerhard (The Plant journal, 2021)
The developmental transition from a fertilized ovule to a dispersed diaspore (seed or fruit) involves complex differentiation processes of the ovule's integuments leading to the diversity in mature seed coat structures in angiosperms. In this study, comparative imaging and transcriptome analysis were combined to investigate the morph-specific developmental differences during outer seed coat differentiation and mucilage production in Aethionema arabicum, the Brassicaceae model for diaspore dimorphism. One of the intriguing adaptations of this species is the production and dispersal of morphologically distinct, mucilaginous and non-mucilaginous diaspores from the same plant (dimorphism). The dehiscent fruit morph programme producing multiple mucilaginous seed diaspores was used as the default trait combination, similar to Arabidopsis thaliana, and was compared with the indehiscent fruit morph programme leading to non-mucilaginous diaspores. Synchrotron-based radiation X-ray tomographic microscopy revealed a co-ordinated framework of morph-specific early changes in internal anatomy of developing A. arabicum gynoecia including seed abortion in the indehiscent programme and mucilage production by the mucilaginous seed coat. The associated comparative analysis of the gene expression patterns revealed that the unique seed coat dimorphism of Ae. arabicum provides an excellent model system for comparative study of the control of epidermal cell differentiation and mucilage biosynthesis by the mucilage transcription factor cascade and their downstream cell wall and mucilage remodelling genes. Elucidating the underlying molecular framework of the dimorphic diaspore syndrome is key to understanding differential regulation of bet-hedging survival strategies in challenging environments, timely in the face of global climatic change.
Keywords: fruit development; sekvenční analýza RNA; Aethionema arabicum; Plant Cells; transkripční faktory; Seeds; semena rostlinná; Plant Proteins; developmental anatomy; buněčná diferenciace; transcription factors; Transcription Factors; bet-hedging; Fruit; seed coat mucilage; rostlinné proteiny; ovoce; reproductive development; Leucine Zippers; Brassicaceae; rostlinné buňky; kyselina abscisová; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; diaspore dimorphism; leucinové zipy; Abscisic Acid; Cell Differentiation; synchrotron radiation X-ray tomographic microscopy; Sequence Analysis, RNA; phenotypic plasticity